The Functional Profile and Antioxidant Capacity of Tomato Fruits Are Modulated by the Interaction between Microbial Biostimulants, Soil Properties, and Soil Nitrogen Status - Paola Ganugi; Andrea Fiorini; Vincenzo Tabaglio; Federico Capra; Gokhan Zengin; Paolo Bonini; Tito Caffi; Edoardo Puglisi; Marco Trevisan; Luigi Lucini (MDPI AG, 2023)
The application of microbial biostimulants to plants has revealed positive effects related to nutrients uptake, stress tolerance, root development and phenological growth. However, little information is available exploiting the potential synergistic biostimulant action of microbes on the functional quality of the yields. The current research elucidated the effect of single or coupled action of biostimulants, associated with either optimal or reduced nitrogen application, on the functional quality of tomato fruits. Chemical assays and untargeted metabolomics were applied to investigate Rhizoglomus irregulare and Funneliformis mosseae administration (both being arbuscular mycorrhiza, AMF), under optimal or low N input conditions, alone or coupled to Trichoderma atroviride application. The coupling of AMF and Trichoderma fungal inoculations resulted in a synergistic biostimulant effect on tomato fruits under sub-optimal fertility, revealing improved concentrations of carotenoid compounds-B-carotene (0.647 ± 0.243 mg/100 g), Z-carotene (0.021 ± 0.021 mg/100 g), 13-z-lycopene (0.145 ± 0.052 mg/100 g) and all-trans-lycopene (12.586 ± 1.511 mg/100 g), and increased values for total phenolic content (12.9 ± 2.9 mgGAE/g), total antioxidant activity (phosphomolybdenum, 0.9 ± 0.2 mmolTE/g), radical scavenging activity (DPPH, 3.4 ± 3.7 mgTE/g), reducing power (FRAP, 23.6 ± 6.3 mgTE/g and CUPRAC, 37.4 ± 7.6 mg TE/g), and enzyme inhibitory activity (AChE, 2.4 ± 0.1 mg GALAE/g), when compared to control. However, evidence of carotenoid and bioactive compounds were exclusively observed under the sub-optimal fertility and no significant differences could be observed between the biostimulant treatment and control under optimal fertility.